Social Media and Spoken English: Analyzing Its Influence on Students' Oral Communication and Linguistic Development - Tagle, Jaycelyn; Rafael, Jullie Anne; Santos, Joseline (Future Science / FSH-PH Publications, 2025)
Purpose – This study examines the influence of social media on students' oral communication skills and linguistic development in English language learning, identifying key research trends and foundational works. Design/methodology/approach – A bibliometric analysis was conducted using 201 peer-reviewed documents from the Scopus database (2010–2025). This dataset reflects influential studies, ensuring high-quality research contributions to technology-enhanced language education. VOS viewer was used to create co-authorship, co-citation, and keyword co-occurrence maps, applying thresholds for citation counts and keyword frequencies to focus on high-impact studies. Findings – The analysis shows growing interest in social media as a tool for enhancing oral proficiency and linguistic competence, with core themes including learner autonomy, digital engagement, language anxiety, and AI-driven tools. Foundational theories like Krashen’s Input Hypothesis and Vygotsky’s Sociocultural Theory were frequently cited, highlighting their relevance in digital language education. Practical implications – The findings suggest that social media can enhance formal education by providing immersive environments for practicing oral communication. Educators are encouraged to integrate social media into curricula to boost motivation, reduce anxiety, and promote real-world language use. Originality/value – This study provides a novel bibliometric synthesis of literature on social media and language development, mapping its intellectual structure and identifying emerging research areas, thus contributing to the discourse on technology-enhanced language education.